Peripheral nerve injuries in the athlete - Feinberg, J. H.; Nadler, S. F.; Krivickas, L. S. (Sports Medicine, 1997)
Peripheral nerves are susceptible to injury in the athlete because of the excessive physiological demands that are made on both the neurological structures and the soft tissues that protect them. The common mechanisms of injury are compression, traction, ischaemia and laceration. Seddon's original classification system for nerve injuries based on neurophysiological changes is the most widely used. Grade 1 nerve injury is a neuropraxic condition, grade 2 is axonal degeneration and grade 3 is nerve transection. Peripheral nerve injuries are more common in the upper extremities than the lower extremities, tend to be sport specific, and often have a biomechanical component. While the more acute and catastrophic neurological injuries are usually obvious, many remain subclinical and are not recognised before neurological damage is permanent. Early detection allows initiation of a proper rehabilitation programme and modification of biomechanics before the nerve injury becomes irreversible. Recognition of nerve injuries requires an understanding of peripheral neuroanatomy, knowledge of common sites of nerve injury and an awareness of the types of peripheral nerve injuries that are common and unique to each sport. The electrodiagnostic exam, usually referred to as the 'EMG', consists of nerve conduction studies and the needle electrode examination. It is used to determine the site and degree of neurological injury and to predict outcome. It should be performed by a neurologist or physiatrist (physician specialising in physical medicine and rehabilitation), trained and skilled in this procedure. Timing is essential if the study is to provide maximal information. Findings such as decreased recruitment after injury and conduction block at the site of injury may be apparent immediately after injury but other findings such as abnormal spontaneous activity may take several weeks to develop. The electrodiagnostic test assists with both diagnosis of the injury and in predicting outcome. Proximal nerve injuries have a poorer prognosis for neurological recovery. The most common peripheral nerve injury in the athlete is the burner syndrome. Though primarily a football injury, burners have been reported in wrestling, hockey, basketball and weight-lifting as a result of acute head, neck and/or shoulder trauma. Most burners are self-limiting, but they occasionally produce permanent neurological deficits. The axillary nerve is commonly injured with shoulder dislocations but is also susceptible to injury by direct compression. The sciatic and common peroneal nerves can be injured by trauma. The suprascapular, musculocutaneous, ulnar, median and tibial nerves are susceptible to entrapment. The long thoracic and femoral nerves can be injured by severe traction.